Westerncentric in the Design of Costumes in Javanese Dance Opera in the XVIII Century - Pramutomo, R. M.; Amelia, Riva (International Journal of Culture and History, 2024)
The 18th century Javanese performance art has given an artistic expression of the aristocrats known as the Langendriya genre. Langendriya’s performing arts are the creativity of the Yogyakarta royal aristocrats who are recognized as the prototype of Javanese opera art. The creator of the Langendriya opera is Prince of Mangkubumi, the younger brother of Sultan Hamengku Buwana VII, the seventh king of the Yogyakarta kingdom. In the process of creation, Prince of Mangkubumi was assisted by his two sons, KRT. Kertanegara and KRT. Wiraguna. Through KRT Wiraguna figure Langendriya opera fashion design gets a European touch by combining Western designs and Javanese designs. This article wants to reveal the uniqueness of the Western design model applied to the Javanese designs created by KRT Wiraguna. As a new creation, the combination of Western and Javanese works by KRT Wiraguna became phenomenal in the 18th century. This article is written using historical methods combined with ethnochoreological methods as the scientific basis for opera drama. Therefore, ethnocoreological analysis will be useful in the application of design in the form of the body of the dance opera that is presented.